Development of polylactide and polypropylene composites reinforced with sisal fibres and halloysite nanotubes for automotive and structural engineering applications - Krishnaiah, Prakash (2017)
In recent decades, scientific research giving more attention to the development of bio-based polymer composites due to the extensive usage of petroleum based fillers as well as polymer matrices for the generation of polymer composites. It is a well-known fact that the petroleum derived polymer composites raise inevitable issues such as environmental pollution, waste management and depletion of petroleum resources etc. So it is important to develop fully or partially biodegradable polymer composites without compromising the mechanical, physical and thermal properties which are required for the end use applications. In this investigation, two different types of filler materials such as sisal fibres and halloysite nanotubes were used to prepare PLA polymer composites and their morphology, physical, mechanical, dynamic mechanical, thermal, water absorption and biodegradable properties were studied. This work also involves the preparation and properties of polypropylene composites reinforced with sisal fibres and halloysite nanotubes to compare the mechanical and thermal properties with PLA composites.